2018
DOI: 10.1148/radiol.2018172783
|View full text |Cite
|
Sign up to set email alerts
|

Use of Screening Mammography to Detect Occult Malignancy in Autologous Breast Reconstructions: A 15-year Experience

Abstract: Purpose To examine how often screening mammography depicts clinically occult malignancy in breast reconstruction with autologous myocutaneous flaps (AMFs). Materials and Methods Between January 1, 2000, and July 15, 2015, the authors retrospectively identified 515 women who had undergone mammography of 618 AMFs and who had at least 1 year of clinical follow-up. Of the 618 AMFs, 485 (78.5%) were performed after mastectomy for cancer and 133 (21.5%) were performed after prophylactic mastectomy. Medical records w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…The patients should therefore be explicitly counseled that native breast tissue is still present in the reconstructed breast and on the need for future routine breast cancer screening. In a large retrospective review of surveillance mammography in patients with postmastectomy autologous breast reconstruction, Noroozian et al 9 found that continued screening was useful in detecting occult malignancy. MRI was found to be more specific in its ability to detect recurrence before clinical appearance and differentiate between malignant and benign findings.…”
Section: Discussionmentioning
confidence: 99%
“…The patients should therefore be explicitly counseled that native breast tissue is still present in the reconstructed breast and on the need for future routine breast cancer screening. In a large retrospective review of surveillance mammography in patients with postmastectomy autologous breast reconstruction, Noroozian et al 9 found that continued screening was useful in detecting occult malignancy. MRI was found to be more specific in its ability to detect recurrence before clinical appearance and differentiate between malignant and benign findings.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of recurrences in the reconstructed breast will be found in the skin and the subcutaneous tissues followed by recurrences deep to the pectoralis muscle [7]. Recurrence rates are reported to be approximately 1% to 2% annually for both mastectomy and mastectomy with reconstruction, and overall recurrence has been reported at between 2% to 15% and has been noted to vary based on the initial cancer type and stage as well as follow-up period of the study [5,[7][8][9][10][11][12][13]. Clinical evaluation has been a mainstay of evaluation of the postmastectomy breast [4], and the appropriate surveillance imaging strategy for patients with a history of mastectomy with or without reconstruction is an evolving topic, with evidence predominantly drawn from small retrospective studies.…”
Section: 2 Ormentioning
confidence: 99%
“…As long as the breast parenchyma has been completely removed during mastectomy, routine mammography on the affected side will not be neces-sary [16]. However it should be noted that some centers will ignore this advice and perform regular mammography in asymptomatic women after mastectomy with or without reconstruction [17]. If there is suspicion of significant residual breast parenchyma after mastectomy, breast MRI can reliably confirm or exclude residual parenchyma.…”
Section: Follow-up After Mastectomymentioning
confidence: 99%